Tokyo Mighty Guy - Saito, Buichi; Takamura, Kuratarô; Kobayashi, Akira; Asaoka, Ruriko; Nakahara, Sanae (Arrow Video, 2016)
In Saito's "Tokyo Mighty Guy", mega star Akira Kobayashi stars as Jiro in the rambunctious tale of a chef who opens a restaurant in the busy Ginza district. His culinary skills and dashing good looks bring in the women as well as unwanted trouble, while an explosive political scandal builds around his girlfriend's business ... [Cover]